PABRIK (Penyuluhan Pembuatan ECOBRICK): Solusi Inovatif Pemanfaatan Sampah Plastik sebagai Upaya Pemberdayaan Masyarakat Desa Taraweang, Kecamatan labakkang, Kabupaten Pangkajene dan Kepulauan: Indonesia - Sabri; Sutamrin; Rosidah; Muh. Ikhwan Risqullah; Mulyani Marhadi (Jurusan Matematika FMIPA UNM, 2023)
Implementation of the Ecobrick Making Education Program (PABRIK) within the framework of the UNM 2023 Community Service Program (KKNT) in Taraweang Village, Pangkajene and Islands Regency, as an innovative solution to overcome the problem of plastic waste. The PABRIK program aims to increase public awareness about plastic waste management and introduce ecobrick production techniques. This article outlines the three stages of the program, including preparation, implementation, and the final stage, which involves education and training in school and community settings. The results show enthusiasm and positive participation from the target community, as well as the successful transformation of plastic waste into valuable products. This program also contributes to efforts to reduce environmental pollution.